The Arabs in America, 1492-1977 : a chronology & fact book - Mehdi, Beverlee Turner, 1930- (Dobbs Ferry, N.Y. : Oceana Publications, 1978)
A history of Arabs in the United States with illustrative documents, appendices, and bibliography
Includes bibliographical refrences (p. 143-146) and index
Keywords: Arab Americans -- History -- Chronology; Arab Americans -- History -- Sources; Arab Americans -- History